Philosophy of State: Social Solidarity and Social Order of a country according to Emile Durkheim - Nur Rohim Yunus (ADALAH, 2019)
In 1858, Emile Durkheim presented a sociological theory of the concept of solidarity. According to Durkheim, solidarity is a bond between individuals and/or groups based on moral values and beliefs, which are developed from shared emotional experiences. Solidarity stresses the state of interaction between individuals and organizations and serves as the basis for a common bond in life that is supported by the moral standards and beliefs of society. The real realization of a partnership will evoke emotional experiences that will strengthen the partnership. Simple civilization has grown into a modern society. Primitive society's social solidarity is different from modern society's solidarity.